Evaluation On The Effect Of Sago/Iota-Carrageenan Microgels Thickeners On Rheology, Texture And Sensory Of Pureed Carrot As Dysphagia Diet - Rozman, Norrazatin Haida (2024)
The inability or difficulty to swallow food and liquids is known as dysphagia. Providing soft, palatable and healthy texture modified foods for these group of people, is a major challenge for the food industry. Due to strong starchy flavour imparted from commercial starch-based dysphagia thickener, a study to develop microgels from other food biopolymers are needed. The objective of this study was to develop sago starch and iota-carrageenan based microgels with a functionality as food thickeners in pureed food. In phase 1, different concentrations of iota-carrageenan were added into sago starch dispersion. Microgels were fabricated using ultrasound treatment followed by spray drying process. A commercial dysphagia thickener that normally used at medical institutions and nursing homes was also included as a reference. Microgels exhibiting varying concentrations of iota-carrageenan demonstrated distinct behaviours in rheological and textural assessments. According to rheological tests, sago/iota-carrageenan microgels showed a predominant elastic tendency, with gʹ>gʺ in the frequency range. According to texture profile analysis (tpa), the sample containing 2.0 g of sago starch and 2.0 g of iota-carrageenan, ms50, exhibited excellent adhesiveness and elastic behaviour compared to a commercial thickener. The usage of sago/iota-carrageenan microgels in texture-modified food as texture modifier was further investigated in phase 2. Different sago/iota-carrageenan microgel concentrations and a commercial thickener were added to pureed carrots, and the textural properties were examined. Thixer, a commercial thickener made of modified corn starch, was used as a reference sample, while pureed carrot without the addition of thickener acts as a control xvi group.